2011
DOI: 10.1007/s10493-011-9486-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to chlorpyriphos in the predatory mite Kampimodromus aberrans

Abstract: The predatory mite Kampimodromus aberrans (Oudemans) is a key biocontrol agent in vineyards in Italy and Southern Europe. Its susceptibility to common pesticides (e.g., organophosphates) has been considered an important factor in preventing successful biocontrol of phytophagous mites. Nevertheless, populations of K. aberrans apparently resistant to organophosphates (OPs) have been reported to occur in Northern Italian vineyards. The resistance of K. aberrans to fungicides (e.g., mancozeb) has been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…A G119S substitution (AChE torpedo numbering) in the single copy AChE gene has been associated with moderate decreases in chlorpyrifos susceptibility between resistant and sensitive strains of T. urticae (resistance ratio at LD50, RR 50 = 31), and a greater resistance ratio in cases of F331W replacement (RR 50 > 400). The K. aberrans strain with the highest level of insensitivity to chlorpyrifos (PO strain) described by Tirello et al (2012) has a RR 50 = 539,602, and this ratio is even higher than that found in the T. urticae populations with the F331W AChE genotype.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…A G119S substitution (AChE torpedo numbering) in the single copy AChE gene has been associated with moderate decreases in chlorpyrifos susceptibility between resistant and sensitive strains of T. urticae (resistance ratio at LD50, RR 50 = 31), and a greater resistance ratio in cases of F331W replacement (RR 50 > 400). The K. aberrans strain with the highest level of insensitivity to chlorpyrifos (PO strain) described by Tirello et al (2012) has a RR 50 = 539,602, and this ratio is even higher than that found in the T. urticae populations with the F331W AChE genotype.…”
Section: Discussionmentioning
confidence: 91%
“…This substitution in the mosquito paralogous AChE seems not to be neutral under the selective pressure produced by organophosphate and carbamate treatments (Weill et al, 2004a). Indeed, when additional two chlorpyrifos-susceptible and three chlorpyrifos-resistant unrelated strains of K. aberrans were identified using a discriminant dose of chlorpyrifos (Tirello et al, 2012), KaAChE genotyping revealed the presence of the G191S substitution only in the resistant strains in the homozygous condition. The silent nucleotide polymorphisms found in the KaAChE cDNA of the resistant strains might also suggest that different G119S mutation events occurred independently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations